Comics Beyond the Page in Latin America. (Modern Americas., 2020)
Comics Beyond the Page in Latin America is a cutting-edge study of the expanding worlds of Latin American comics. Despite lack of funding and institutional support, not since the mid-twentieth century have comics in the region been so dynamic, so diverse and so engaged with pressing social and cultural issues. Comics are being used as essential tools in debates about, for example, digital cultures, gender identities and political disenfranchisement. Rather than analysing the current boom in comics by focusing just on the printed text, however, this book looks at diverse manifestations of comics 'beyond the page'. Contributors explore digital comics and social media networks; comics as graffiti and stencil art in public spaces; comics as a tool for teaching architecture or processing social trauma; and the consumption and publishing of comics as forms of shaping national, social and political identities. Bringing together authors from across Latin America and beyond, and covering examples from Argentina, Brazil, Colombia, Mexico, Peru and Uruguay, the book sets out a panoramic vision of Latin American comics, whether in terms of scholarly contribution, geographical diversity or interdisciplinary methodologies.